2022
DOI: 10.3389/fcvm.2022.869585
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperthermia as a trigger for Takotsubo syndrome in a rat model

Abstract: Takotsubo syndrome is a well-characterized cause of acute yet reversible heart failure associated with periods of intense emotional stress, often mimicking on presentation an acute coronary syndrome. Animal models of Takotsubo syndrome have been developed, either through the application of a stressor, or administration of exogenous catecholamine. We found that in a model of isoproterenol-induced Takotsubo syndrome in anesthetized rats hyperthermia (40–41°C) would occur after the administration of isoproterenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This addresses the limitation of uncontrolled drug levels in the bloodstream associated with IP injections. Additionally, hyperthermic conditions ( 23 ) are unnecessary in this model, and it accurately replicates key TS features across sexes ( 86 ). The onset is acute, peaking at 4–6 h, followed by a recovery phase at 24 h. Rats recover in cardiac function and contractility within 1–14 days, with the majority recovering within 48–72 h. At 30 days, all surviving rats show normal behaviour, ECG, and imaging.…”
Section: Animal Models Of Takotsubo Syndromementioning
confidence: 97%
See 1 more Smart Citation
“…This addresses the limitation of uncontrolled drug levels in the bloodstream associated with IP injections. Additionally, hyperthermic conditions ( 23 ) are unnecessary in this model, and it accurately replicates key TS features across sexes ( 86 ). The onset is acute, peaking at 4–6 h, followed by a recovery phase at 24 h. Rats recover in cardiac function and contractility within 1–14 days, with the majority recovering within 48–72 h. At 30 days, all surviving rats show normal behaviour, ECG, and imaging.…”
Section: Animal Models Of Takotsubo Syndromementioning
confidence: 97%
“…Not everyone develops TS following a stressful event, suggesting that a variety of factors influence its development. Some reported factors are related to thyroid function ( 21 ), climatic and body temperatures ( 22 , 23 ), malignancy ( 24 ), as well as age, sex, and neurological and psychiatric disorders.…”
Section: Clinical Characteristics Of Takotsubo Syndromementioning
confidence: 99%
“…This hypothesis is supported by an in silico modelling study that recreated Takotsubo-like contractile dysfunction with apical dysfunction following intense agonist stimulation when apical-basal β 1 AR and β 2 AR gradients were introduced [ 41 ]. Further, TTS-like dysfunction can be induced in vivo by bolus injection adrenaline or isoprenaline [ 20 , 21 , 42 , 43 , 44 ]. Interestingly, the hyperthermic response subsequent to catecholamine administration seems necessary for the induction of TTS, since a recent in vivo study demonstrated that maintenance of hyperthermia would induce TTS-like contractile dysfunction following isoprenaline administration, whereas active cooling prevented, but did not reverse, these changes [ 43 ].…”
Section: Cardiomyocyte Contractility and The Adrenergic Systemmentioning
confidence: 99%
“…Further, TTS-like dysfunction can be induced in vivo by bolus injection adrenaline or isoprenaline [ 20 , 21 , 42 , 43 , 44 ]. Interestingly, the hyperthermic response subsequent to catecholamine administration seems necessary for the induction of TTS, since a recent in vivo study demonstrated that maintenance of hyperthermia would induce TTS-like contractile dysfunction following isoprenaline administration, whereas active cooling prevented, but did not reverse, these changes [ 43 ].…”
Section: Cardiomyocyte Contractility and The Adrenergic Systemmentioning
confidence: 99%
“…Hyperthermia has been recently suggested as a possible trigger for TTS, via a rise in body temperature due to a catecholamine storm ( 88 ). We propose that orexin influences this cascade, as emerging evidence suggests it plays a role in thermoregulation ( 89 ) and in regulating the HPT-axis ( 20 ).…”
Section: Alternative Explanatory Framework For Pathophysiology Of Tts...mentioning
confidence: 99%